Industrial heritage as a culturally sustainable option in urban transformation: The case of Skien and Moss - Swensen, Grete; Skrede, Joar (FormAkademisk, 2018)
Industrial heritage represents an opportunity for architects and designers to combine a building’s robust form with creative solutions. A former methanol factory in Skien used as art hall, and a former paper mill in Moss used as a music venue, exemplify the ways in which cultural provisions for a diverse urban population can be accommodated. We examined the kinds of cultural provisions industrial buildings offer and how industrial heritage’s tolerance level is met. The results are discussed in light of the societal responsibility to find long-lasting, sustainable solutions in urban development.